2023
DOI: 10.3390/biomedicines11092401
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Faceted Role of Cancer-Associated Adipocytes in Colorectal Cancer

Adriana Grigoraș,
Cornelia Amalinei

Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed types of cancer, especially in obese patients, and the second cause of cancer-related death worldwide. Based on these data, extensive research has been performed over the last decades to decipher the pivotal role of the tumor microenvironment (TME) and its cellular and molecular components in CRC development and progression. In this regard, substantial progress has been made in the identification of cancer-associated adipocytes’ (CAAs) characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…These dysfunctional adipocytes and infiltrated immune cells in the adipose tissue secrete diverse cytokines and adipokines that provoke a pro-inflammatory microenvironment and remodel the extracellular matrix, thereby providing a favorable microenvironment for cancer growth and metastasis [10,18,19]. Furthermore, studies have shown that adipocytes near the cancer-invasive front are transformed into small-sized cells showing fibroblast-like features, which then release pro-inflammatory cytokines and chemokines, increase glucose metabolism, and provide fatty acids to cancer cells as energy fuel [20,21]. These modified adipocytes are referred to as cancer-associated adipocytes, and they are now considered to have crucial impacts on cancer growth, metastasis, and angiogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dysfunctional adipocytes and infiltrated immune cells in the adipose tissue secrete diverse cytokines and adipokines that provoke a pro-inflammatory microenvironment and remodel the extracellular matrix, thereby providing a favorable microenvironment for cancer growth and metastasis [10,18,19]. Furthermore, studies have shown that adipocytes near the cancer-invasive front are transformed into small-sized cells showing fibroblast-like features, which then release pro-inflammatory cytokines and chemokines, increase glucose metabolism, and provide fatty acids to cancer cells as energy fuel [20,21]. These modified adipocytes are referred to as cancer-associated adipocytes, and they are now considered to have crucial impacts on cancer growth, metastasis, and angiogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that adipocytes near the cancer-invasive front are transformed into small-sized cells showing fibroblast-like features, which then release pro-inflammatory cytokines and chemokines, increase glucose metabolism, and provide fatty acids to cancer cells as energy fuel [20,21]. These modified adipocytes are referred to as cancer-associated adipocytes, and they are now considered to have crucial impacts on cancer growth, metastasis, and angiogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…CAAs promote metabolic reprogramming and chemoresistance in colon cancer cells. CAAs release adipokines and metabolic factors to regulate the immune response of anti-tumor immune cells ( Harmon et al, 2019 ; Grigoras and Amalinei, 2023 ). CAAs contribute to the formation of a low-grade chronic inflammatory environment conducive to tumorigenesis, the mechanism being that CAAs influence the TME by releasing pro-inflammatory factors IL-1β, IL-6, IL-8, and TNF-α ( Grigoras and Amalinei, 2023 ).…”
Section: Ginsenosides Modulate Matrix Cells and Matrix Components In ...mentioning
confidence: 99%
“…CAAs release adipokines and metabolic factors to regulate the immune response of anti-tumor immune cells ( Harmon et al, 2019 ; Grigoras and Amalinei, 2023 ). CAAs contribute to the formation of a low-grade chronic inflammatory environment conducive to tumorigenesis, the mechanism being that CAAs influence the TME by releasing pro-inflammatory factors IL-1β, IL-6, IL-8, and TNF-α ( Grigoras and Amalinei, 2023 ). In addition, CAAs are frequently located at the front of invasive colorectal cancer, exhibiting a fibroblast-like phenotype, and establish a bidirectional molecular dialogue with colorectal tumor cells, leading to functional changes in normal cells and promoting CRC invasion ( Munteanu et al, 2020 ).…”
Section: Ginsenosides Modulate Matrix Cells and Matrix Components In ...mentioning
confidence: 99%